MANAJEMEN PRIVASI KOMUNIKASI MAHASISWA UPN VETERAN JAKARTA PADA FITUR CLOSE FRIEND DI INSTAGRAM - Fiona Azzahra; Lusia Handayani; Vina Mahdalena (Jurnal Pustaka Komunikasi, 2022)
The development of features on social media does not escape the risks, as happened with the close friends feature on Instagram. One of the problems that occurs is the leakage of information submitted, but the case of information leakage does not dampen the desire of individuals to continue to use it. Therefore, this study aims to find out how students experience managing and controlling their privacy information on the close friends feature and to find out why they use it. This study uses a qualitative research method with a phenomenological approach to find out more deeply a person's experience of a phenomenon. Researchers collected data by conducting in-depth interviews with 7 (seven) UPN Veteran Jakarta students from various faculties and produced 7 (seven) themes in the student experience using the close friend feature on Instagram. The data analysis techniques used in this study include the collection of life experiences, horizontalization, significant statements, thematic analysis, and essence statements. The results of this study found that there was a motive made by UPN Veteran Jakarta students in using the close friend feature on Instagram, namely they felt free to express themselves so they were comfortable in sharing information about themselves. In addition, they are also not fixated on the displayed image or other users' responses to their uploads.